2007
DOI: 10.1007/s00228-007-0423-0
|View full text |Cite
|
Sign up to set email alerts
|

Ritodrine pharmacokinetics in twin pregnancy patients

Abstract: Due to a decrease in total body clearance in three of the 14 patients, overall serum concentration of ritodrine increased at the end of the pregnancies. To further characterize ritodrine kinetics, additional studies are needed to determine an effective and safe therapy for ritodrine use in twin pregnancy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…While working on a method for the effective use of ritodrine in long-term tocolysis, we developed a procedure to measure the concentration of unchanged ritodrine, and reported a difference of approximately three-fold in the value of the clearance of unchanged ritodrine in some cases. 8) Ritodrine is metabolized mainly to sulfate and glucuronide conjugates, with the ritodrine conjugates having no pharmacological activity. [9][10][11][12] It was considered that the concentration of unchanged ritodrine varied with the decline or increase in the conjugation reaction, thus influencing the effectiveness on uterine muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While working on a method for the effective use of ritodrine in long-term tocolysis, we developed a procedure to measure the concentration of unchanged ritodrine, and reported a difference of approximately three-fold in the value of the clearance of unchanged ritodrine in some cases. 8) Ritodrine is metabolized mainly to sulfate and glucuronide conjugates, with the ritodrine conjugates having no pharmacological activity. [9][10][11][12] It was considered that the concentration of unchanged ritodrine varied with the decline or increase in the conjugation reaction, thus influencing the effectiveness on uterine muscle.…”
Section: Discussionmentioning
confidence: 99%
“…7) In addition, 3 of the 14 mothers enrolled in that study showed a negative correlation with regard to gestational age and the clearance of unchanged ritodrine. 8) Changes in maternal physiology caused by the continuation of twin pregnancy are considered to be one of the reasons. 8) And it was shown that twin pregnancy mothers had a significantly lower systemic clearance of ritodrine than singleton pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ballabh et al 6) reported that the half-life of betamethasone is significantly longer in singleton than in twin pregnancies ( reported that the weekly increase in daily dose of insulin between weeks 14 and 27 is two times higher in twin pregnancies compared with singleton. We previously reported that ritodrine clearance decreases as twin pregnancies progress 8) . However, the effects of ritodrine pharmacokinetics and number of fetuses on delivery outcomes have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness correlation and pharmacodynamics for the treatment of threatened abortion and the measured serum concentration of racemic ritodrine has been previously demonstrated (1,2). Linear pharmacokinetic behavior and decreased clearance of retodrine diastereomers that are commercially available have been found in the late gestation period in twin pregnancy patients (3).…”
Section: Introductionmentioning
confidence: 99%